HIF-1 α as a Key Factor in Bile Duct Ligation-Induced Liver Fibrosis in Rats. (2nd January 2017) - Moczydlowska, Joanna; Miltyk, Wojciech; Hermanowicz, Adam; Lebensztejn, Dariusz M.; Palka, Jerzy A.; Debek, Wojciech
ABSTRACT: Background: Although several studies suggested hypoxia as an important microenvironmental factor contributing to inflammation and fibrosis in chronic liver diseases, the mechanism of this process is not fully understood. We considered hypoxia inducible factor (HIF-1α) as a key transcription factor in liver fibrosis. The aim of the study was to evaluate the mechanisms of signaling pathway during bile duct ligation (BDL)-induced liver fibrosis in rats. Methods: BDL animal model of liver fibrosis was used in the study. Male Wistar rats were divided randomly into two experimental groups: sham group ( n = 15), BDL group ( n = 30). Hydroxyproline (Hyp) content as a marker of collagen accumulation in liver of rats subjected to BDL was evaluated according to the method described by Gerling B et al. Expression of signaling proteins [integrin β1 receptor, HIF-1α, nuclear factor kappa B (NF-κB), and transforming growth factor (TGF-β)] was evaluated applying Western-immunoblot analysis. In all experiments, the mean values for six assays ± standard deviations (SD) were calculated. The results were submitted to the statistical analysis using the Student's " t " test, accepting p < 0.05 as significant. Results: Ligation of bile ducts was found to increase Hyp content in rat liver, accompanied by increase of HIF-1α expression during 10 weeks after BDL. The Hyp level was time dependent. There was not such a difference in control group ( p < 0.001). Simultaneously expression of NF-κB, TGF-β, β1 -integrin receptor was significantly elevated starting from sixth week after ligation. Activity of metalloproteinases 2 and 9 in the livers were increased 1 week after surgery and remained increased until the end of the experiment. Conclusions: The mechanism of development of liver fibrosis involves activation of Matrix metalloproteinase-2 (MMP-2) and Matrix metalloproteinase-9 (MMP-9), upregulation of HIF-1α transcriptional activity and its related factors, NF-κB and TGF-β. It suggests that they may represent targets for the treatment of the disease.